The Effect of Remittance on Consumption and Household Assets in Indonesia - Cahyanti, Alif Dewi; Sugiharti, Lilik (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2022)
International migration is the process of moving people from one country to another. There is a close relationship between migration and consumption behavior. Migration can be considered as an alternative to improve consumption patterns. The impact of international migration is quite large for the area of origin, one of which is the flow of remittances for the area of origin. Remittance also increases the welfare of recipient households that can increase their income and consumption. This study uses panel data sourced from Indonesian Family life Survey (IFLS) 4 and 5 in 2007 and 2014. using the Ordinary Least Square (OLS) method. results show Ordinary Least Square (OLS) that remittances are significant and have a positive relationship with food consumption, non-food and total food and ownership of assets